HIV‑1 drug‑resistance mutations and related risk factors among HIV‑1‑positive individuals receiving first-line antiretroviral therapy - Elvira, Dwitya; Rahayuningsih, Sri Puji; Nadia, Rizka; Masri, Raveinal (Faculty of Medicine, Universitas Trisakti, 2025)
Background Acquired immunodeficiency syndrome (AIDS) remains a global health issue. Antiretroviral therapy (ART) controls HIV progression, but widespread use had led to drug resistance mutations (DRMs) such as M184V and K103N, compromising treatment efficacy. This study assessed the prevalence of these mutations and identified associated risk factors in patients with first-line nucleoside reverse transcriptase inhibitor (NRTI)-based ART. Methods A cross-sectional study was conducted involving 80 HIV patients aged > 18 years who had been on NRTI and non-NRTI (NNRTI) therapy for >6 months. Data included sociodemographic characteristics, ART adherence, opportunistic infections, viral load, CD4 count, treatment duration, ART regimen, and presence of M184V and/or K103N mutations. Genetic analysis was performed and statistical associations were assessed using simple and multivariate logistic regression. Results M184V and/or K103N mutations were detected in 8 patients (10%), significantly associated with poor ART adherence (p<0.01), detectable viral load (p<0.01) and male gender (p=0.048), but not with age (p=0.653), body mass index (p=0.661), opportunistic infections (p=0.938), CD4 count (p=0.265), and treatment duration (p=0.365). Multivariate logistic regression analysis showed that poor ART adherence was associated with a decreased risk of mutations compared to good adherence (OR = 0.73, 95% CI:0.012-0.427) and male patients had a 10-fold higher risk compared to females (OR = 10.03, 95% CI:1.033-97.350). Conclusion This study demonstrated that male gender was significantly associated with an increased risk of mutations, while poor ART adherence showed an unexpected inverse association. Strengthening adherence support programs remains essential to preventing drug resistance mutations and ensuring treatment efficacy.